A PASSIVE STRATEGY FOR MANAGEMENT OF COUNTERACTION TO ENCROACHMENTS ON BUSINESS ORGANIZATION: A PASSIVE STRATEGY FOR MANAGEMENT OF COUNTERACTION TO ENCROACHMENTS ON BUSINESS ORGANIZATION - Нristov , Нristo (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
From the point of view of one social organization a rational choice about an alternative for an action in a definite security environment is made on the basis of defining optimum of possible numbers of alternatives among which a choice is being fulfilled towards putting into practice a system of criteria in order to compare options of alternatives. For that reason taking a decision connected with a choice about a strategy for management of counteraction to encroachments on social organization is one of the most difficult management tasks that has ever been carried out on the circumstances of complex and dynamic fast-changing security environment.